Pengaruh DER dan ROA Terhadap Harga Saham yang Terdaftar di Indeks IDX30 - Geraldine, Frederica; Elizabeth, Sri Megawati (Universitas Multi Data Palembang, 2024)
This study aims to determine the effect of Debt to Equity Ratio and Return On Asset on stock prices listed on the IDX30 index. The scope of this study is to discuss how the Effect of Debt to Equity Ratio and Return On Asset on the price of shares listed on IDX30. The research method used in this study is quantitative method. The type of data used in this study is secondary data. The sample in this study amounted to 13 companies using purposive sampling. Data testing using the help of the SPSS 22 application. The results showed that Debt to Equity Ratio has an influence on stock prices and Return On Assets has an influence on Stock Prices.